Marketing of Mango: Perceived constraints during normality and due to lockdown in West Bengal - Roy, Rakesh; Das, Suddhasuchi; Sarkar, Victor; Das, Bhabani; Mondal, Adwaita; Rudra, B.C.; Bhowmik, Paramita; Majumder, Debjyoti (Indian Journal of Extension Education, 2021)
The study was undertaken to assess the perceived constraints in marketing of mango during normality and due to lockdown in West Bengal. In all, 90 respondents were randomly considered for the study with equal proportionate of small, medium and large farmers. The perceived constraints faced and suggestions in improving the marketing of mangoes were analyzed through Garrett ranking techniques. The study shows that the major perceived constraints in marketing of mangoes during normality were high fluctuation in market price during season followed by inadequate marketing channel and exploitation by middlemen. But during the lockdown, the major perceived constraints were no market to sell their mangoes followed by exploitation by middlemen and small opening hours of market. The suggestive measures recommended by the mango growers to improve marketing opportunities were stable market rate according to grade of mangoes followed proper marketing channel and elimination of middlemen. The mangoes growers had not felt need for cooperative marketing network or formation of Farmer Producer Company for its marketing.Â